Potential impact of land redistribution on the South African economy - Mukarati, Julius (My University, 2023)
Natural resource ownership programmes are introduced as a way of improving income distribution and alleviating poverty in rural areas that are mostly in developing countries. These ownership programmes range from fishing rights ownership to rural land redistribution programmes under which rural land redistribution is the most dominant and common policy in developing countries. In the case of South Africa, land redistribution policies are still being implemented in line with the national development plan targeting extreme poverty alleviation and reduction of wide income disparities by the year 2030. Although the policies can be regarded as effective, they may have diverging effects on economic growth, poverty, and income distribution mostly in developing countries. Land redistributive policies can be viewed as effective tools for reducing rural poverty mainly because agriculture continues to be a major source of rural livelihood and a contributor to rural economic growth. Theoretically, agricultural land reform significantly contributes towards poverty alleviation through increased average income, improved income distribution, increased crop yield, and demand for export-oriented agricultural products, thereby increasing the overall welfare of smallholder farmers. Empirically, in most developing countries, the impacts of redistributive policies have mostly been analysed using static economy-wide computable general equilibrium (CGE) models. Although these models are widely used in assessing the impacts of these economic policies, the potential overall policy impacts comprising short-run, long-run and detailed distribution effects and the over-time behavioural response to policy shifts are not adequately captured. The economic structural changes and economy-wide impacts need to be assessed and captured over time. A South African Social Accounting matrix can be used as a data base to construct a dynamic CGE model to simulate the potential impact on household welfare in South Africa. A dynamic model will be appropriate because rural land redistribution is a long-term investment, while simulation is essential for detailed distributional analysis of poverty. Although several studies have been conducted on the impacts of rural land redistribution policies in South Africa, in the researcher’s knowledge, none of them have applied a dynamic CGE model to assess the poverty impacts, especially of the proposed government rural land redistribution policy. Essentially, the empirical rural land redistribution studies accounted for neither the dynamics nor distributive effects for a detailed poverty analysis of the rural land redistribution programme due to the static nature of the model. Therefore, this study seeks to assess how government redistributive policies may affect household welfare in the short and long-run, focusing on poverty and income distribution in South Africa by applying a dynamic CGE model.The empirical results showed that there is a strong connection between the agriculture sector and household income as rural households mostly derive their income from agricultural activities. This implies that any policy that targets the agriculture sector will have an impact on rural household income. Contrary to the general view that rural land redistribution in developing countries is disinclined to poverty and income inequalities, the study established that properly implemented rural land redistribution coupled with government support is an important strategic policy in poverty reduction with long-term economic benefits. The study also identified the various channels through which rural land redistribution impacts rural household income. It can be noted that poorer households are the net direct beneficiaries of rural land redistribution, particularly through factor returns. It can be foreseen that improving household access to productive land could be key to sustainable and inclusive economic growth in South Africa. The results support the claim that rural land redistribution coupled with agriculture investment and government support can be effective in improving household welfare. It is recommended that the South African government should increase investment towards land beneficiaries as a way of boosting agriculture production.
Thesis (Ph.D. (Commerce in Economics)) -- University of Limpopo, 2023
Keywords: Computable general equilibrium; Microsimulation; Poverty; Income distribution; Income distribution -- South Africa; Poverty -- South Africa; Land reform -- South Africa